Onthel Bicycle: Creation Model of Experimental Photography using Iwan Zahar Method - I Made Dennis Penn Yohan Kayansa; I Nengah Wirakesuma (Institut Seni Indonesia Denpasar, 2023)
In Indonesia, the development of bicycles was heavily influenced by the colonialists, especially the Dutch. They brought bicycles produced in their country to use around to enjoy the fresh nature of Indonesia. This habit was transmitted to the aborigines with blue blood. Finally, the bicycle became a prestigious means of transportation. Onthel bicycles were a means of transportation that were relatively expensive before the independence period. Onthel bicycles, also known as camel bicycles, kebo bicycles, or pit pancal, are standard bicycles with 28-inch tires that were commonly used by urban communities until the 1970s. The heritage factor and the classic shape of the bicycle are interesting to be used as an experimental bicycle photography work. Starting from this phenomenon, the authors argue that research related to bicycles is necessary and interesting to do because in the globalization or modern era which is full of modern lifestyle offers, bicycles actually choose a classic lifestyle.